Rekonstruksi Penafsiran Ayat-Ayat Amtsal Tentang Kaum Munafik: Studi Pemikiran Muh}ammad ‘Abduh dalam Tafsir Al-Manar - Nunung Lasmana (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2017)
Amtsal is one of the redaction diversity and uslub al-Qur'an which is very interesting because it is the media of divine messages transformation order to more quickly get to the soul. The metaphor verses provides an opportunity that is wide enough to be interpreted. However, in interpreting the Qur'an need to contextualise and actualization of that Qur'an feels more alive. And one of commentary books with contextual model is Tafsir al-Manar. When it is compared with the works of other commentators, the Muhammad 'Abduh's work give high appreciation of the study of the verses that is categorized as amtsal so in this study were directed to examine the interpretation of amtsal mus}arrah}ah verses in Tafsir al-Manar especially those of the hypocrites. The interpretation presented by 'Abduh about the hypocrites differ with the interpretation of the scholars in general. Some scholars built hypocritical concept on the understanding of theology, while the interpretation of 'Abduh built on the pattern adabi ijtima‘i thus giving birth to a new understanding of the concept of the hypocrites in the Qur'an.